Composition of Theophany on X-XI cc. Georgian Church Facades - Silagadze, Nino (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2017)
The present paper is an attempt to analyze some samples of Georgian medieval architecture, a small group of monuments which we believe to be outstanding for their facade decoration. i.e. churches built in the 10th- 11th centuries, the facades of which are decorated with figu- rative relief compositions of the Savior’s Glorification, the Second Coming of Christ and Theophany.